1990
DOI: 10.1177/0013161x90026002003
|View full text |Cite
|
Sign up to set email alerts
|

The Dimensionality of Decision Participation in Educational Organizations: The Value of a Multi-Domain Evaluative Approach

Abstract: While the literature on education reform has called for increased teacher participation in decision making, little is known about the decision participation construct itself Previous research in this area may be categorized according to the approach taken with respect to the conceptualization and operationalization of participation in decision making. We argue that an approach which views the construct as both evaluation-based and multi-dimensional in nature has advantages over three other common approaches ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 24 publications
7
77
0
Order By: Relevance
“…However, this result is consistent with other studies throughout this study and also cited in the present study (Bacharach et al, 1990;Mohrman et al,1978;Brown & Hunter, 1998, Everett, 1998Geraghty, 1997;Hopkins, 1999, Peters, 1999. Further, there are studies Taylor and Bogotch (1994) cited in which student learning outcomes are not the focus of restructuring efforts (Elmore, 1993;Wohlstetter & Odden, 1992).…”
Section: Teacher Empowerment and Involvement In School-based Decisionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, this result is consistent with other studies throughout this study and also cited in the present study (Bacharach et al, 1990;Mohrman et al,1978;Brown & Hunter, 1998, Everett, 1998Geraghty, 1997;Hopkins, 1999, Peters, 1999. Further, there are studies Taylor and Bogotch (1994) cited in which student learning outcomes are not the focus of restructuring efforts (Elmore, 1993;Wohlstetter & Odden, 1992).…”
Section: Teacher Empowerment and Involvement In School-based Decisionsupporting
confidence: 94%
“…The dependent variable for the study was decision participation as measured by an unnamed instrument previously used by Conley (1990), but adapted from Bacharach et al (1990), having a Cronbach alpha of .81.…”
Section: Teacher Empowerment and Involvement In School-based Decisionmentioning
confidence: 99%
“…Review of literature reveals that most research examined the relationship between teachers' participation in decision making and organizational commitment [3]. This fact is supported by the recent study conducted by Somech and Bogler [35] who identified that the participation in the managerial domain is positively associated with organizational commitment.…”
Section: B Teachers' Participation In Decision Making and Commitmentmentioning
confidence: 94%
“…Although recent studies have largely ignored the issue of consensus in the role of the teacher, a good deal of research has recently appeared on role conflicts that are perceived by teachers (see Bacharach, Bamberger, & Conley, 1990;Bacharach, Bamberger, Conley, & Bauer, 1990;Bacharach, Bamberger, & Mitchell, 1990;Bamberger & Hasgall, 1995;Billingsley & Cross, 1992;Byrne, 1994;Clift et aI., 1992;Crane & Iwanicki, 1986;Litt & Turk, 1985;PiersonHubeny & Archambault, 1985;Schwab & Iwanicki, 1982;Schwab, Jackson, & Schuler, 1986;Stamaman & Miller, 1992;and Thomas, 1991).…”
Section: Role Conflicts and Related Issues For Teachersmentioning
confidence: 99%
“…Many of these studies (and others) have also recently explored teachers' experiences of role ambiguity (see Bacharach, Bamberger, & Conley, 1990;Bacharach, Bamberger, Conley, & Bauer, 1990;Bacharach, Bauer, & Conley, 1986;Billingsley & Cross, 1992;Clift et aI., 1992;Crane & Iwanicki, 1986;Pierson-Hubeny & Archambault, 1985;Schwab & Iwanicki, 1982;Stamaman & Miller, 1992;and Thomas, 1991). These latter studies suggest that the experience of role ambiguity may also be widespread among some teachers, and when the latter occurs, it is also associated with negative outcomes such as depersonalization, reduced accomplishment, lowered job satisfaction, and reduced occupational commitment.…”
Section: Role Conflicts and Related Issues For Teachersmentioning
confidence: 99%